Selective Boryl‐Anion Migration in a Vinyl sp2−sp3 Diborane Induced by Soft Borane Lewis Acids. (6th September 2018) - Fasano, Valerio; Cid, Jessica; Procter, Richard J.; Ross, Emily; Ingleson, Michael J.
Abstract: An intramolecular 1, 2‐boryl‐anion migration from boron to carbon has been achieved by selective activation of the π system in [(vinyl)B2 Pin2 )] − using "soft" BR3 electrophiles (BR3 =BPh3 or 9‐aryl‐BBN). The soft character is key to ensure 1, 2‐migration proceeds instead of oxygen coordination/B−O activation. The BR3 ‐induced 1, 2‐boryl‐anion migration represents a triple borylation of a vinyl Grignard reagent using only B2 Pin2 and BR3 and forms differentially protected 1, 1, 2‐triborylated alkanes. Notably, by increasing the steric bulk at the β position of the vinyl Grignard reagent used to activate B2 Pin2, 1, 2‐boryl‐anion migration can be suppressed in favor of intermolecular BPin − transfer to BPh3, thus enabling simple access to unsymmetrical sp 2 −sp 3 diboranes. Abstract : Die selektive Aktivierung des π‐Systems in einem vinylischen sp 2 ‐sp 3 ‐Diboran mit „weichen" Boran‐Lewis‐Säuren führt zur intramolekularen Migration eines 1, 2‐Borylanions von einem Bor‐ zu einem Kohlenstoffatom (siehe Schema) – im Gegensatz zu Sauerstoffkoordination und B‐O‐Aktivierung. Diese Reaktion ermöglichte die dreifache Borylierung eines vinylischen Grignard‐Reagens zur Bildung unterschiedlich geschützter 1, 1, 2‐triborylierter Alkene.